Administration of equine Chorionic Gonadotrophin (eCG) to rams to improve the reproductive performance during the non-breeding season - Beracochea, Florencia; Manes, Jorgelina; Viera, Maria Noel; Santiago-Moreno, Julian; Ungerfeld, Rodolfo (Elsevier, 2020)
In most ram breeds, there are annual changes in testosterone serum concentration and semen quality. This study aimed to determine if eCG administration to rams during the non-breeding season improves the reproductive activity. In the first study, we compared the effects of administering three doses of eCG (0, 400 or 700 IU). In the second experiment we compared the effects of administering eCG to rams from two breeds originated in different latitudes, and thus, with different expected reproductive seasonal pattern (Highlander; HL and Texel; TEX). The first study was performed during the mid non-breeding season with three groups of rams: treated with 400 IU (group eCG400) or 700 IU of eCG (group eCG700), or untreated controls (group CON). Treated rams received three doses of eCG administered every 6 days. Testosterone concentration, testicular traits (scrotal circumference, testicular and sexual skin flush, and ultrasonographic testes pixel color intensity) and seminal characteristics were determined from five days before the first eCG administration until Day 24. Testosterone concentration was greater in eCG700 than in eCG400 (P <0.001) and CON (P <0.0001) rams, and in eCG400 than in CON rams (P = 0.0002). However, the treatment did not modify the testicular traits and seminal quality. The second study was performed with 15 HL and 17 TEX rams; while 8 HL and 9 TEX rams received two doses of 1000 IU of eCG (Days 0 and 5), the other rams remained as untreated controls. Scrotal circumferences, seminal traits (fresh and thawed semen, and cryopreservation ratio –CR-) as well as the sexual behavior were determined, twice before eCG administration and during 3 weeks. The treatment did not modify the scrotal circumference nor the fresh sperm traits evaluated. However, the CR of motile and progressive motile sperm were greater in eCG treated rams than in control rams on Day 7 (P = 0.01 for both). Treated rams had their second and third ejaculations earlier than control rams (P = 0.001 and P = 0.02; respectively). In conclusion, the administration of eCG during the non-breeding season stimulated testosterone secretion without modifying the main reproductive outcomes of rams. Reducing the interejaculatory intervals could be considered for intensive semen collection programs.